2022
DOI: 10.3389/fphys.2022.991320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methionine and trace minerals (zinc, copper and manganese) supplementation on growth performance of broilers subjected to Eimeria challenge

Abstract: Coccidiosis is a major intestinal challenge that causes economic loss to the broiler industry. Two battery cage studies were conducted to evaluate the effect of trace minerals, source and dose of methionine on growth performance and gut health of broilers subjected to Eimeria challenge. Experiment #1 consisted of 9 treatments of 2 × 2 × 2 factorial design + 1 arrangement with main factors of methionine (Met) sources (DL-Met vs. 2-hydroxy-4-(methylthio)-butanoic acid (HMTBa)), total sulfur amino acid (TSAA) lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Trace inorganic nutrients are important for physiological functions (growth, development, and health) in broilers [ 91 ]. The deficiency of these essential nutrients may result in reduced synthesis of enzymes and proteins such as collagen, a main component of feathers and beaks, and keratin, a structural protein of the extracellular matrix and connective tissue [ 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trace inorganic nutrients are important for physiological functions (growth, development, and health) in broilers [ 91 ]. The deficiency of these essential nutrients may result in reduced synthesis of enzymes and proteins such as collagen, a main component of feathers and beaks, and keratin, a structural protein of the extracellular matrix and connective tissue [ 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more poultry producers are looking into natural approaches to control coccidiosis, such as essential oils, probiotics, prebiotics, trace minerals, and other gut health enhancing products, which could be complimentary to the coccidiosis control programs. Chen et al (2022) showed that supplementation of both bis-chelated mineral methionine hydroxy analog chelates (MMHAC) and high levels of total sulfur amino acid could overcome the growth performance challenges due to coccidiosis. It has been reported that Cu requirements were higher for chickens experiencing an acute phase response or pathological challenge compared to healthy chickens (Koh et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The most serious limitation to the drugs' effectiveness is the development of resistance [4][5][6]. Therefore, many studies have used alternative methods, such as plant extracts, vitamins, and minerals, to control and treat the disease [7][8][9].…”
Section: Introductionmentioning
confidence: 99%